2020
DOI: 10.1002/smtd.202000265
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Radiation Synthesis of Ultrafine Platinum Nanoclusters toward Methanol Oxidation

Abstract: Direct methanol fuel cells (DMFCs) are considered as a promising candidate for portable electronic devices and small electric vehicles due to their high gravimetric and volumetric energy densities. The operation of DMFCs requires efficient catalysts, especially on the anode to promote methanol oxidation reaction (MOR). To date, platinum has emerged as a chief contender for MOR. Unfortunately, most catalysts suffer from severe CO poisoning, which can passivate the catalytic surface and decrease the activity ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The precursor-loaded material was transferred onto the heater, a stripe of carbon nanotube film that was connected to a homemade sample holder. [26,27] By applying different currents through the heater for radiative Joule-heating, the Pt formed and anchored onto the support (See the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…The precursor-loaded material was transferred onto the heater, a stripe of carbon nanotube film that was connected to a homemade sample holder. [26,27] By applying different currents through the heater for radiative Joule-heating, the Pt formed and anchored onto the support (See the Experimental Section for details).…”
Section: Resultsmentioning
confidence: 99%
“…Representative research endeavors have demonstrated the potential of pulsed heating methods in directing reaction time scales and pathways, thereby enabling the synthesis of specialized solid catalysts and other functional materials. For instance, the controllable preparation of single-crystal Pt foil, Pt nanocluster, , and Pt single-atom catalyst can be achieved by reducing the Joule heating duration from hours to milliseconds. This is due to the limited heating time, which kinetically constrains the nucleation and growth of Pt or the diffusion of thermally activated Pt atoms.…”
Section: Catalyst Fabrication By Pulsed Heatingmentioning
confidence: 99%
“…(b 3 ) Pt clusters. Reproduced with permission from ref . Copyright 2020 John Wiley & Sons, Inc. (b 4 ) Pt SAs.…”
Section: Catalyst Fabrication By Pulsed Heatingmentioning
confidence: 99%
“…31,32 Though the easy operation of the latter enables it to be applied in large-scale synthesis, it may require proper control of the sintering and cooling process as the nucleation, growth, and aggregation of nanoparticles (NPs) are all time-dependent diffusion processes. 33 Thus, a hightemperature shock (HTS) method, a process driven by the instantaneous high temperature from the Joule effect, has received increasing attention in the past few years. The high temperature can accelerate the diffusion process of the NPs while the transient heating and ultrafast cooling effectively avoid agglomeration of the NPs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At present, there are two main ways to synthesize carbon-loaded Pt-based alloys. One is to reduce the precursors of metal salts before loading them onto the carbon support, which is convenient for precise control of the morphology. The other way is to reduce the precursors wet-impregnated onto the carbon support. , Though the easy operation of the latter enables it to be applied in large-scale synthesis, it may require proper control of the sintering and cooling process as the nucleation, growth, and aggregation of nanoparticles (NPs) are all time-dependent diffusion processes . Thus, a high-temperature shock (HTS) method, a process driven by the instantaneous high temperature from the Joule effect, has received increasing attention in the past few years.…”
Section: Introductionmentioning
confidence: 99%